Anticandidal Efficacy of Cinnamon Oil Against Planktonic and Biofilm Cultures of Candida parapsilosis and Candida orthopsilosis - Pires, Regina Helena [UNESP]; Montanari, Lilian Bueno; Martins, Carlos Henrique G.; Zaia, Jose Eduardo; Almeida, Ana Marisa Fusco [UNESP]; Matsumoto, Marcelo T. [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Springer, 2011)
Candida parapsilosis is yeast capable of forming biofilms on medical devices. Novel approaches for the prevention and eradication of the biofilms are desired. This study investigated the anticandidal activity of sixteen essential oils on planktonic and biofilm cultures of C. parapsilosis complex. We used molecular tools, enumeration of colony-forming units, the colourimetric MTT assay, scanning electron microscopy (SEM) and a chequer-board assay coupled with software analyses to evaluate the growth kinetics, architecture, inhibition and reduction in biofilms formed from environmental isolates of the Candida parapsilosis complex; further, we also evaluated whether essential oils would interact synergistically with amphotericin B to increase their anticandidal activities. of the environmental C. parapsilosis isolates examined, C. parapsilosis and C. orthopsilosis were identified. Biofilm growth on polystyrene substrates peaked within 48 h, after which growth remained relatively stable up to 72 h, when it began to decline. Details of the architectural analysis assessed by SEM showed that C. parapsilosis complex formed less complex biofilms compared with C. albicans biofilms. The most active essential oil was cinnamon oil (CO), which showed anticandidal activity against C. orthopsilosis and C. parapsilosis in both suspension (minimum inhibitory concentration-MIC-250 and 500 mu g/ml) and biofilm (minimum biofilm reduction concentration-MBRC-1,000 and 2,000 mu g/ml) cultures. CO also inhibited biofilm formation (MBIC) at concentrations above 250 mu g/ml for both species tested. However, synergism with amphotericin B was not observed. Thus, CO is a natural anticandidal agent that can be effectively utilised for the control of the yeasts tested.
Keywords: C. parapsilosis; Biofilms; Essential oils; Cinnamon oil; Anticandidal agents